Do health investments improve agricultural productivity: Lessons from agricultural household and health research - McNamara, Paul E.; Ulimwengu, John M.; Leonard, Kenneth L. (International Food Policy Research Institute, 2011)
The link between good health and economic prosperity is well established and can be detected in numerous measures, such as increased income, wages, efficiency, and productivity. While the link can readily be seen in descriptive statistics, however, it is another matter to disentangle the precise nature of the connection. It is likely that causality runs in both directions, and both health and prosperity clearly are affected by numerous other variables.